New neighborhood, old habits? Delivery preferences of residents in new development areas and their assessment of alternative parcel logistics concepts: A case study of Berlin - Johannes Gruber; Benjamin Heldt; Saskia Seidel (Journal of Shipping and Trade (JST), 2023)
Various alternative solutions for sustainable last-mile parcel deliveries have been piloted and partially put into operation in Europe in the past decade. However, these delivery concepts have mainly been considered in inner-city areas. There are a few examples of the application of these concepts in peripheral urban areas, where new housing is being built to accommodate high population pressure. However, it is unclear whether the delivery preferences of residents in new neighbourhoods differ from those of the population average. This research conducted a case study in the western outskirts of Berlin, examining two newly built neighbourhoods and one existing residential area. Results from three survey waves of residents (N=645) show that conventional doorstep delivery is preferred by 80% of the respondents. Nonetheless, there is a high willingness to use alternative delivery options, and respondents see benefits in climate-friendly delivery methods. This research also examines the willingness to pay for alternative parcel logistics concepts, which seems to be too low at the moment (at around exteuro1 per shipment) to compensate for the additional costs of an operational change. However, the results also show an increasing awareness of and preferences for new delivery concepts, thus providing practical implications for planners and logistics operators alike.
Keywords: 650; Delivery preferences; Empirical survey; Last-mile delivery; Logistics concepts; Micro-depot; New development areas; Online shopping; Parcel locker; Urban logistics